2019
DOI: 10.1108/afr-10-2018-0096
|View full text |Cite
|
Sign up to set email alerts
|

The impact of credit on productivity of smallholder farmers in Ghana

Abstract: Purpose The purpose of this paper is to evaluate the impact of access to production credit on the productivity of smallholder farmers. Design/methodology/approach Data for the study were drawn from the Agricultural Value Chain Facility (AVCF), which was implemented in the Northern Region of Ghana. This paper uses the Propensity Score Matching (PSM) to estimate the average treatment effect of access to production credit on the productivity of smallholder farmers. The rationale for the choice of this estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
(33 reference statements)
2
31
0
Order By: Relevance
“…Simtowe and Zeller (2006) found that access to credit increased adoption of hybrid maize among credit-constrained agricultural households in Malawi. Similar results are found in numerous other studies including (Abdallah, 2016;Akudugu, 2016;Iddrisu et al, 2017;Nordjo and Adjasi, 2019).…”
Section: Introductionsupporting
confidence: 92%
“…Simtowe and Zeller (2006) found that access to credit increased adoption of hybrid maize among credit-constrained agricultural households in Malawi. Similar results are found in numerous other studies including (Abdallah, 2016;Akudugu, 2016;Iddrisu et al, 2017;Nordjo and Adjasi, 2019).…”
Section: Introductionsupporting
confidence: 92%
“…Furthermore, access to credit is also considered to be an important tool for smoothing consumption, promoting production and reducing vulnerability to poverty especially for poor households (Dobridge, 2018; Thanh et al ., 2019; Sun et al ., 2020). Recently in Ghana, studies that have looked at access to credit and savings among smallholder farmers have been biased towards examining the determinants that influence smallholder access to credit and savings (see for example Asante-Addo et al , 2017; Sekyi et al ., 2019; Nordjo and Adjasi, 2019; Twumasi et al , 2019; Aidoo-Mensah, 2019). Moreover, the combined effect of savings, credit and insurance in the Ghanaian literature is scanty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nordjo and Adjasi (2020) used a propensity score matching technique to assess the impact of credit on productivity in Ghana using two control groups and found that better access to credit led to an increase in productivity through investment in farm inputs. The impact was more pronounced for the control group with better credit access.…”
Section: The Literaturementioning
confidence: 99%